2013
DOI: 10.1149/05011.0539ecst
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior and Solvation Analysis of Rare Earth Complexes in Ionic Liquids Media Investigated by SECM and Raman Spectroscopy

Abstract: In this study, the electrochemical behavior of neodymium complexes; Nd(III) in the phosphonium ionic liquid; P2225TFSA triethyl-pentyl-phosphonium bis(trifluoromethylsulfonyl)amide was examined by the voltammetric method using a platinum tip electrode. The diffusional behavior of Nd(III) was certificated to be similar behavior of other rare earth complexes such as Sm. The ideal steady-state approach current of the positive feed back was obtained in Nd(III)/P2225TFSA and the fitted function of this approach cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
(21 reference statements)
2
13
0
Order By: Relevance
“…In the case of dissolving Nd(TFSA) 3 pure salts in TFSA-based ILs, the neodymium TFSA-complex; [Nd(TFSA) 5 ] 2À was identified in the ILs by Raman spectroscopy [23]. It (b) Intensity / a.u.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…In the case of dissolving Nd(TFSA) 3 pure salts in TFSA-based ILs, the neodymium TFSA-complex; [Nd(TFSA) 5 ] 2À was identified in the ILs by Raman spectroscopy [23]. It (b) Intensity / a.u.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…For the development of recycling process of Nd-Fe-B components, it is very important to establish a novel recovery process with energy-saving. For this purpose, we have previously demonstrated an electrodeposition method for Fe [6,7], Nd [7][8][9][10][11][12] and Dy [13,14] metals using room-temperature ionic liquids (RTILs) with the bis(trifluoromethyl sulfonyl)amide, [NTf 2 ] -, anion. RTILs have several distinctive properties such as low vapor pressures, incombustibility, high ionic conductivity, and a wide electrochemical window [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to establish a recovery process of Nd and Dy from the spent Nd-Fe-B magnets in order to provide a steady supply of RE resources. For this purpose, our research group has already demonstrated the electrodeposition method of Nd [8][9][10][11][12] and Dy [13,14] metals using room-temperature ionic liquids (RTILs), which have several distinctive properties such as low vapor pressure, incombustibility, high ionic conductivity and a wide electrochemical window [15,16]. In particular, the RTIL composed of phosphonium cation with short alkyl chain and bis(trifluoromethylsulfonyl)amide anion; [TFSA]…”
Section: Introductionmentioning
confidence: 99%
“…In general, it was known that the electrodeposition process was remarkably affected by the solvation structure of metal ion in ILs. It was reported that the solvation structures of various metal ions, Li [19][20][21][22][23], Mn [24,25], Fe [26], Co [24,26], Ni [24,26], Zn [24], Nd [10,27], Eu [28] and Dy [29] ions in [TFSA]-based ILs were evaluated by Raman spectroscopy and DFT calculation. It has also revealed that the solvation structures and the electrochemical behaviors of trivalent Nd and Dy cations in order to reveal the electrodeposition mechanism in our previous study [14].…”
Section: Introductionmentioning
confidence: 99%